PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI PRODUK MAKANAN KUCING DI MANOKWARI - Makarius Bajari; Cindy Irianti Mongan; Nurwidianto Nurwidianto (Cakrawala Management Business Journal, 2023)
ABSTRACT Cat food is a special food consumed by cats to meet the nutritional needs of cats. The purpose of this study was to determine the effect of the promotion variable and price variable on the variable of buying interest in cat food products (case study of Animalia Vet Store Manokwari). This type of research uses a quantitative approach with the type of associative research. The population in this study were consumers who had purchased cat food at Animalia Vet Store Manokwari, with a research sample of 100 respondents. The sampling technique used purposive sampling. The data analysis method used in this research is multiple linear regression analysis. The results showed that promotion had a partial effect on product purchase intention and price had no partial effect on product purchase intention. Simultaneously promotion and price affect the interest in buying the product. Keywords :Cat food, Promotion, Price, Interested in buying products